Systemic candidiasis in farm-reared red-legged partridges (Alectoris rufa) caused by Leucosporidium spp - Lanteri Giovanni; Macrì Francesco; Rapisarda Giuseppe; Basile Florinda; Reale Stefano; Marino Fabio (BMC Veterinary Research, 2012)
Abstract Background This report describes the results of radiological, histological and molecular examination of three farm-reared red-legged partridges (Alectoris rufa) affected by candidiasis. Case presentation Three juvenile farm-reared red-legged partridges in a batch of 100 of the same species were sent for clinical and pathological investigations. The owner referred of a sudden isolation of the sick animals, with apathy, diarrhea, ruffled plumage and respiratory rattles. Post mortem total body lateral projection radiograph showed an increased perihilar interstitial pattern and air bronchogram signs due to lung edema. At necropsy, carcasses showed cachexia; the pericloacal region was soiled by diarrheic fecal material. From the mouth to the intestine, a mucous yellowish fluid was present on a slightly reddish mucosa. Histopathology showed slight edema and congestion with different free fungal elements, referable to blastospores, hyphae and pseudohyphae. Biomolecular exam identified the most similar sequences as belonging to Leucosporidium scottii. Conclusion To our knowledge, this case report describes for the first time this fungal species as a causative agent of candidiasis in birds.